The Awareness Of Smart Home Security System In Malaysian Household - Ahmad Hadi, Azman (Universiti Malaysia Sarawak, (UNIMAS), 2023)
In recent years, technology has made life simpler and more comfortable. The smart home has evolved into one of the brilliant technologies and concepts that assist residents in living in a better environment. The purpose of this study is to conduct a thorough analysis of Malaysian households' awareness about smart home security systems. The study examines awareness of smart home systems in Malaysia, considering factors like definition, environment, legal and policy issues, security application, and implementation challenges. This research will be conducted by analysing published articles and a survey response to home owners. In this study, the quantitative method will be utilized. The data analysis will disclose Malaysians' household degree of exposure to smart security home system in two ways: a) The general knowledge of the system and b) Implementation of the system. According to this, the likelihood of Malaysians to adopt smart home security systems can be justified. This research is anticipated to enlighten the understanding of the limitations of smart homes for security purposes, enhancing understanding of security systems, network operations, and potential improvements in devices and applications.